Using A modified quickert procedure combined with prolapsed fat and preseptal orbicularis muscle removal to correct involutional lower eyelid entropion in Asians - Chau-Yin Chen; Chien-Hsiung Lai; Yen-Chang Chu; Yi-Lin Liao; Jin-Jhe Wang; Wei-Dar Chen; Yueh-Ju Tsai (Biomedical Journal, 2023)
Purpose: To propose a modified Quickert procedure combined with prolapsed fat and preseptal orbicularis muscle removal which corrects involutional lower eyelid entropion, and to validate the procedure as an adequate surgical management according to anatomical deformities and pathogenesis of Asian patients. Methods: Ninety-five patients (45 men, 50 women; 108 eyelids [55 right eyes, 53 left eyes]) who underwent this modified surgical procedure with a minimum follow-up period of 2 months were examined. All pre- and post-operative evaluations and surgical procedure were performed exclusively from the same oculoplastic surgeon. Postoperative results, recurrence rate, and complications were assessed. Results: The mean follow-up period was 13.33 months (range, 2–67 months). Of the 108 eyelids, 4 developed recurrent entropion with trichiasis, corresponding to an overall recurrence rate of 3.70%. No major complications, such as overcorrection (ectropion), symblepharon, infection, or wound dehiscence, occurred during the follow-up period after surgery. Of these 4 eyelids exhibiting recurrence, 3 occurred within 10 months and 1 occurred 49 months after surgery. Three recurrent patients received secondary surgery for re-correction with successful results. Conclusion: The modified Quickert procedure combined with prolapsed fat and preseptal orbicularis muscle removal not only demonstrated safety and effectiveness, but also led to low rate of recurrence and complications. It could be a strategy for correction of involutional entropion in Asian patients.